Status Hukum Mengkonsumsi Daging Buatan In-Vitro Ditinjau dari Kehalalannya - Muhammad Rizqi Fauzi; Isroqunnajah Isroqunnajah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The development of modern food technology has given rise to innovation in the form of artificial meat (in vitro meat) produced through cell culture techniques in laboratories. This innovation was initiated as a solution to the increasing demand for animal protein and the limited supply of conventional meat. However, its existence has sparked debate regarding its halal status from a contemporary Islamic jurisprudence perspective. This study used a literature study method by analyzing Islamic jurisprudence literature, religious fatwas (fatwas), halal regulations, and scientific studies related to the production process of cultured meat. The results show that the law on consuming in vitro meat is a khilafiyah issue. Some Islamic scholars and international fatwa institutions, such as the International Islamic Fiqh Academy, the Islamic Religious Council of Singapore, and the Fatwa of the Mufti of the Kingdom of Malaysia, permit the consumption of in vitro meat provided that the cells come from halal animals slaughtered according to Islamic law and the production process is free from impure and harmful elements. In contrast, the Nahdlatul Ulama (NU) National Conference of Religious Scholars (Munas Alim Ulama) determined that cell-based meat is haram (forbidden) because the cells are taken from live animals without slaughter, thus creating carcasses. The culture process involves impure materials such as blood serum. In conclusion, the halal status of cultured meat depends heavily on the cell source, production procedures, and the cleanliness of the supporting materials, necessitating a more comprehensive Sharia standard to assess the halal status of this modern food technology. Keywords: Legal Status, Artificial meat, In-vitro meat, Halal